The relevance of viral culture based methods for the detection of rat cytomegalovirus (RCMV all-03) in the modern era of technology - Camalxaman, Siti Nazrina; Allaudin, Zeenathul Nazariah; Quah, Yi Wan; Loh, Hwei San; Hassan, Zuridah; Abdul Rahman, Sheikh Omar; Mohd Lila, Mohd Azmi (Veterinary Association Malaysia, 2011)
In spite of the unequivocal advantages of traditional virological methods, its utilization seems to have taken a back seat coincident with the concurrent advances in science and technology. This study examined the impact of such techniques in the groundwork identification of rat cytomegalovirus ALL-03 strain. Virus was validated in terms of its intrauterine novelty, cytopathogenicity and was identified based on morphologic criteria classical of herpesvirus. Our findings demonstrate the suitability of primary brain endothelial cells for the propagation of the virus resulting in concomitant production of cytopathic effects and formation of plaques comparable to the ones produced in established secondary cell lines. In the absence of any known sequences for molecular based detection method, such findings provided critical clues crucial for the preliminary identification of the virus. This paper concludes that conventional methods such as tissue culture and electron microscopy are still in the forefront in the field of virology and remains relevant, but should ideally be used in conjunction with more advanced methodologies for a more comprehensive evaluation of novel viruses.